Determinants of small business activity and entrepreneurship: household survey evidence from Lithuania. (13th May 2008) - Luke, Peter; Pileckiene, Dalia; Romilly, Peter; Sliziene, Gelmine
This paper identifies and evaluates a number of factors influencing small business activity and entrepreneurship in Lithuania. It is based on a quantitative approach, using a large household labour force survey obtained from the Lithuanian Statistical Office. The size of the sample enables us to determine the influence of a range of factors including age, gender, ethnicity, location, economic sector and occupation, on small business formation and entrepreneurship. The sample size also implies that we can have some confidence in the reliability of the estimation results. The data set is analysed using two probit model specifications. Overall, our results suggest a number of important issues for policy makers seeking to promote the micro and small business sector in Lithuania.